О повышении экономичности паровых турбин с противодавлением - Капинос, Василий Максимович; Навроцкий, В. В.; Михайлова, Ирина Александровна; Михайленко, Т. И. (НТУ "ХПИ", 2004)
The question on use of steam turbines stages with the reduced reactions degree gradient is considered with the purpose of efficiency increase due to reduction the losses connected to leakings of environment through overbandage backlashes in flowing parts of turbines with rather short blades.
Keywords: проточные части турбин; закрутки лопаток; степень реактивности; угол наклона лопаток; градиент давления; КПД турбин